Evaluation of the Effectiveness of Pain Management Training for Nurses in Improving the Quality of Patient Care - Nia Mardalisna; Rahmi Ferdilla Rafli (CV. Get Press Indonesia, 2024)
Pain management is an important part of clinical practice, and it has a significant impact on the quality of patient care. The aim of this study was to evaluate the effectiveness of pain management training for nurses in improving patient care quality. Methods. This is a cross-sectional study that aims to provide evidence-based recommendations that can be used by healthcare institutions to improve nursing training in the future. The research instruments consist of pre-test and post-test questionnaires to measure nurses' knowledge, attitudes, and skills related to pain management. The results of bivariate analysis showed that the comprehensive and theory-based training materials successfully enriched nurses' understanding of the pain management concepts, assessment, and interventions. The mean knowledge score increased from 65.2 10.4 to 85.6 7.8 (31.2% increase; p 0.001). The mean skill score also improved by 32.5% (from 62.8 9.3 to 83.2 8.0) (32.5% increase, p > 0.001), and the mean patient satisfaction score increased by 72.5 6.7 to 91.4 4.9 (26.1% increase; 26% increase). Conclusion. This study proves that theory- and simulation-based learning is not only relevant but also effective in improving patients' quality of care through strengthening nurses' competencies. In addition, the results also provide recommendations for the development of nursing education policies that focus on improving practical skills through evidence-driven approaches and clinical simulations.